2024
DOI: 10.1101/2024.05.07.24306897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Efficacy and Potential of Large Language Models for Depression: A Systematic Review

Mahmud Omar,
Inbar Levkovich

Abstract: Background and Objective: Depression is a substantial public health issue, with global ramifications. While initial literature reviews explored the intersection between artificial intelligence (AI) and mental health, they have not yet critically assessed the specific contributions of Large Language Models (LLMs) in this domain. The objective of this systematic review was to examine the usefulness of LLMs in diagnosing and managing depression, as well as to investigate their incorporation into clinical practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Recent research has shown that LLMs can accurately identify emotions and mental disorders, such as schizophrenia, depression, and anxiety, and provide treatment recommendations and prognoses comparable to mental health professionals. [15][16][17][18][19][20][21][22][23][24][25][26][27] Despite their potential to democratize clinical knowledge and encourage ideological pluralism, 21,28,29 ethical concerns persist. These include data privacy, algorithmic opacity, threats to patient autonomy, risks of anthropomorphism, technology access disparities, corporate concentration, deep fakes, fake news, reduced reliance on professionals, and amplification of biases.…”
Section: Ai-based Technology In Mental Healthmentioning
confidence: 99%
“…Recent research has shown that LLMs can accurately identify emotions and mental disorders, such as schizophrenia, depression, and anxiety, and provide treatment recommendations and prognoses comparable to mental health professionals. [15][16][17][18][19][20][21][22][23][24][25][26][27] Despite their potential to democratize clinical knowledge and encourage ideological pluralism, 21,28,29 ethical concerns persist. These include data privacy, algorithmic opacity, threats to patient autonomy, risks of anthropomorphism, technology access disparities, corporate concentration, deep fakes, fake news, reduced reliance on professionals, and amplification of biases.…”
Section: Ai-based Technology In Mental Healthmentioning
confidence: 99%